Informal food systems at risk: Agrarian changes and rural food security in Lower Gangetic Basin, Bangladesh - Ahsan Habib; Md Sayed Uddin; Jalihah Md Shah (Malaysian Journal of Social Sciences and Humanities (MJSSH), 2025)
Agrarian transformations in Bangladesh’s Lower Ganges Basin, influenced by neoliberal policies, population growth, and environmental shifts, are reshaping rural livelihoods and food security landscapes. This study investigates how shrinking arable land impacts informal food sources—such as wild plants, uncultivated crops, and natural fisheries— that have historically sustained small-scale and landless farmers. Through a qualitative methodology incorporating in-depth interviews and ethnographic observation, this research reveals the essential role these informal food resources play for rural communities as formal agriculture recedes. Field insights show that modern agricultural practices driven by neoliberal policies and commercialization disrupt these informal food systems, which are increasingly relied upon amid diminishing arable land. Research participants shared their struggles adapting to industrial agriculture, underscoring the need to preserve natural food sources as buffers against food insecurity. The study advocates for balanced policies that protect these informal food systems while accommodating agricultural progress. Findings have significant implications for food security policies and rural development in Bangladesh and other countries centered around the Ganges River, especially concerning the resilience of vulnerable communities.